Solid waste management in southern Brazil - Kirchner, Rosane Maria; Silinske, Jaqueline; Benetti, Joana Kirchner; Chaves, Magda Antunes de; Scherer, Mônica Elisa; Saidelles, Ana Paula Fleig; Essi, Liliana (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2013)
http://dx.doi.org/10.5902/2236117010744 A large amount of solid waste generated by the population leads to social, environmental and health problems, so it is important that the Brazilian municipalities have programs for solid waste management in order to reduce the effects of the mismanagement of these materials. Thus, the aim of this study was to characterize the solid waste management in southern Brazil. For data analysis, was used descriptive statistics. The data were obtained from IBGE, referring to the National Survey of Sanitation - year 2008. With this study, it was revealed that all the municipalities in southern Brazil have solid waste management, but there is no selective collection in 52.4% of the municipalities of Paraná State, 66.6% of the municipalities of Santa Catarina State and 66.5% the municipalities of Rio Grande do Sul State. In Brazil, the largest daily quantity of solid waste is destined for landfills, corresponding to 64.6%. Therefore, it is necessary constantly invest in solid waste management, with the aim of improving the services provided to the population and minimize social, environmental and health damage caused by improper management of solid waste.